L-2-hydroxyglutaric aciduria: characterisation of the molecular defect in a spontaneous canine model. Issue 5 (2nd May 2007) - Penderis, Jacques; Calvin, Jacqui; Abramson, Carley; Jakobs, Cornelis; Pettitt, Louise; Binns, Matthew M; Verhoeven, Nanda M; O'Driscoll, Eamonn; Platt, Simon R; Mellersh, Cathryn S
Abstract : l -2-hydroxyglutaric aciduria (l -2-HGA) is a neurometabolic disorder that produces a variety of clinical neurological deficits, including psychomotor retardation, seizures and ataxia. The biochemical hallmark of l -2-HGA is the accumulation of l -2-hydroxyglutaric acid (l -2-HG) in cerebrospinal fluid, plasma and urine. Mutations within the gene L2HGDH (Entrez Gene ID 79944) on chromosome 14q22 encoding L-2-hydroxyglutaric acid dehydrogenase have recently been shown to cause l -2-HGA in humans. Using a candidate gene approach in an outbred pet dog population segregating l -2-HGA, the causal molecular defect was identified in the canine homologue of L2HGDH and characterised. DNA sequencing and pedigree analysis indicate a common founder effect in the canine model. The canine model shares many of the clinical and MRI features of the disease in humans and represents a valuable resource as a spontaneous model of l -2-HGA.